(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The teaching skills and techniques of a pedagogue in professional education, where professional education is considered adult education, educational work is focused on child education and training of future educators. Increasing the effectiveness of the lesson, making effective use of the time allocated to the lesson, increasing students’ interest and passion for the lesson. Ensuring the participation of all students in the lesson at the same time.